Analisis Kandungan Siklamat dan Sakarin pada Minuman Es Kopi Susu Gula Aren di 5 Coffee Shop, Kota Bandar Lampung - Sugiarty, Alviany Mayska; Fithriyani, Dina; Wahyuningtyas, Amalia (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Sumatera, 2022)
Changes in consumer lifestyles in Indonesia have led to an increase in coffee consumption in Indonesia. This has triggered an increasing number of coffee drink producers with various innovations, such as one of the coffee menus that consumers generally prefer, namely iced coffee, milk, palm sugar. Based on the study of the use of sweeteners, 61.36% were dominated by beverage products and sweeteners that were often used, namely cyclamate and saccharine. This study aims to determine the use of cyclamate and saccharin in iced coffee drinks with palm sugar milk in 5 coffee shops in Bandar Lampung which were analyzed by one sample t-test with α = 5%. The results obtained showed that all samples only contained cyclamate with a content exceeding the maximum limit of cyclamate use (350 mg/kg) without the use of saccharine. Keywords: Coffee, Cyclamate, Saccharine